Seroprevalence and Socio-demographic Factors of Helicobacter pylori Infection in Patients with Dyspepsia in Kalibaru Primary Health Care North Jakarta - Nikko Darnindro; Ari F Syam; Achmad Fauzi; Cleopas M Rumende (Acta Medica Indonesiana)
Aim: to identify the seroprevalence and its association with socio-demographic factors of Helicobacter pylori infection. Methods: a cross-sectional study was performed in 111 patients with dyspepsia (according to ROME III) who got treatment at Kalibaru Primary Health Care, North Jakarta from January to February 2015. Patients aged over 18 years and no history of gastrectomy were interviewed and 3 cc venous blood was drawn. Bioramps Laboratories’s Immunochromatography Diagnostic Test (Bio M Pylori®) was used to diagnose patient with Helicobacter pylori infection. Chi Square were used to analyzed socio-demographic and T test were used to analyze age. Variables with p<0.25 were analyzed by logistic regression. Results: seroprevalence of Helicobacter pylori of 111 dyspepsia patients who got treatment in Kalibaru Primary Health Care in this study was 22.5% (95% CI 14.8% - 30.2%). There is no relation between age and Helicobacter pylori infection (p=0.270). Higher socio-economic class was related to lower risk Helicobacter pylori infection (OR 0.2; 95% CI 0.02 – 1.71). Higher crowding index was related to higher risk Helicobacter pylori infection (OR 1.2; 95% CI 0.37 – 4.49). Lower clean water index was related to higher risk Helicobacter pylori infection (OR 1.5; 95% CI 0.57 – 4.04). Lower sanitation status was related to higher risk Helicobacter pylori infection (OR 2.5; 95% CI 1.01 – 6.19). Conclusion: seroprevalence of Helicobacter pylori infection in patient with dyspepsia in Kalibaru village was 22.5%. There is an association between sanitation and Helicobacter pylori infection.